Rare Association between Two Genetic Conditions: Turner Syndrome and Neurofibromatosis Type 1 - R. El Qadiry; K. Danaoui; H. Nassih; A. Bourrahouat; I. Ait Sab (Case Reports in Endocrinology)
Turner’s syndrome (TS) is a sex chromosome disorder due to loss of either all or part of the X chromosome, in some or all the cells of the body. Neurofibromatosis type 1 (NF-1) is a multisystemic genetic disorder that is only rarely observed in association with Turner syndrome. Only six cases of Turner syndrome associated with NF-1 have been reported in the literature. In this study, we report the first case with TS and NF-1 in a Moroccan child. Case Report. A 16-year-old female was born of a nonconsanguineous marriage. In her family history, her mother had multiple café-au-lait spots with Lisch nodules on ophthalmologic examination. She was diagnosed with TS (karyotype: 45, X) due to short stature and characteristic features. The diagnosis of NF-1 was made according to the presence of four diagnostic criteria of the National Institute of Health Consensus Development Conference. Conclusion. Coexistence of NF-1 with TS is rare. We consider that this may be the seventh case report of TS associated with NF-1.